Heart rate variability in regular season and play-off competitions in professional archers - Yuan, S. C.; Huang, Y. F.; Chang, C. K. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Archery is a precision close-circuit sport. Archers have to adjust their arousal level under competition pressure for optimal performance. Heart rate variability (HRV) represents the balance between autonomic nervous system. The purpose of this study is to investigate heart rate variability before and during regular-season and play-off competitions in professional archers. METHODS: Four male and four female archers from a professional team in Chinese Enterprise Archery League were recruited. The participants wore a portable HRV device (Largan Health AI-tech, Taichung, Taiwan) before and during League competitions from April to October, 2023. HRV data during the 30-min period before the competitions (B) and the 15-min period during the competitions (D) were analyzed. Overall, 12 regular season (RE) and 6 play-off (PO) competitions were included. RESULTS: During RE competitions, heart rate (HR) was significantly increased from before competition (B:95.37±11.59; D:110.11±15.51 bpm, p<0.001) while low-frequency power (LF) (B:43571.5±20867.0; D:19203.6±12634.7, p<0.001), high-frequency power (HF) (B:9733.2±6478.1; D:5403.6±3900.3, p<0.001), and LF/HF ratio (B:5.50±2.67; D:4.50±2.92, p=0.020) were significantly decreased. During PO competitions, HR was significantly increased from before competition (B:99.44±11.14; D:111.62±15.01 bpm, p<0.001) while LF (B:37288.0±23012.8; D:15819.7±10135.6, p=0.000), HF (B:8691.3±7340.9; D:4280.0±3831.6, p<0.001) were significantly decreased. Pre-competition HR was significantly higher in PO than RE (RE:95.37±11.59; PO:99.44±11.14 bpm, p=0.040) while root mean square of successive differences between normal heartbeats (RMSSD) (RE:66.65±26.95; PO:56.27±28.74, p=0.031) and standard deviation of the normal-normal interval (SDNN) (RE:82.87±19.68; PO:74.14±22.25, p=0.016) were significantly decreased. During-competition rMSSD (RE:63.41±28.04; PO:53.43±26.45, p=0.036) SDNN (RE:79.25±19.16; PO:71.09±21.11, p=0.019) were significantly lower in PO than RE. CONCLUSION: The results showed that professional archers had a significant increase in heart rate and a noticeable decrease in sympathetic and parasympathetic nervous system activity during RE and PO competitions. It suggested that professional archers perceived higher tension and stress even though they tried to suppress arousal. The lack of difference in LF/HF before and during PO competitions indicated that the participants experienced higher stress and pressure The participants exhibited a significant decrease in relaxation level and autonomic nervous system activity in PO compared to regular season matches, experienced higher stress and pressure, possibly due to the close association with final rankings. Individualized stress adaptation training may be necessary for these group of elite archers for optimal performance in competitions.